Optimalisasi Penggunaan Media Sosial Bagi Kalangan Remaja di SMA Negeri 1 Panga Aceh Barat - Agatha Debby Reiza (Jurnal Pengabdian Masyarakat: Darma Bakti Teuku Umar, 2019)
Advances in technology make it easier for humans in their activities. The internet has become mandatory for use in various aspects of life. Social media users in Indonesia reach 150 million people. Most internet users are aged 15 to 19 years, which is 91%. At present the way to get along with teenagers is not only by direct contact but also indirectly by using media or social networking. The use of social media is sometimes difficult to control either by parents or the school, so there is a need for education for adolescents to be more optimal in using social media for anything positive. The purpose of this mass empowerment activity is to provide understanding to teenagers that social media can provide many positive benefits if we use it in a smart and maximum way, and invites young people to be smart in using social media. The implementation method is through counseling and discussion with high school students 1 Panga. The results of this activity turned out that not all students have social media both Facebook and Instagram because of limitations in accessing. Before this activity the participants only used social media as a means of uploading photos and videos, but after this activity they learned that social media can be used optimally namely to carve out achievements and as a medium to increase personal finances.